2018
DOI: 10.5817/cp2018-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Who is involved in cyberbullying? Latent class analysis of cyberbullying roles and their associations with aggression, self-esteem, and empathy

Abstract: The present analyses empirically explored the roles in cyberbullying by using Latent Class Analysis. Potential predictors of class membership were also examined using multinomial logistic regression analysis. Participants were 849 German students (52.7% girls, 45.6% boys, Mage = 13.4 years, SDage = 1.1 years). Observed indicators of latent class measured own involvement in cyberbullying, reactions to cyberbullying of classmates, and behavioral willingness as assistant and as defender. Indicators for the post-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 69 publications
(82 reference statements)
7
66
2
Order By: Relevance
“…However, they differ with respect to the composition and percentage of subjects included. The prevalence of "not involved" subjects obtained in this study is much lower than findings from past studies [13][14][15]17,20] which found rates of 52% to 77% of adolescents who were not involved in the cyberbullying cases. However, the percentage found by Betts et al (2017), in a sample of youth aged 16 to 19 (33%) is higher [16].…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…However, they differ with respect to the composition and percentage of subjects included. The prevalence of "not involved" subjects obtained in this study is much lower than findings from past studies [13][14][15]17,20] which found rates of 52% to 77% of adolescents who were not involved in the cyberbullying cases. However, the percentage found by Betts et al (2017), in a sample of youth aged 16 to 19 (33%) is higher [16].…”
Section: Discussioncontrasting
confidence: 86%
“…Another discrepancy is found for the "bully-victim" profile, with the percentage of victims and bullies varying substantially from one study to another. So, we find studies that have a similar prevalence to that of our study [13] while in others [12,14,15,17] the prevalence of this profile is much lower (3-12%). The third profile found in this study, the "rarely victim and bully" group, is characterized by being involved to a greater degree in all of the cyberbullying behaviors (victimization, aggression, and aggression-victimization) as compared to the not-involved group, but not at the levels that are typical of the "bully-victim" group (high cyberbullying).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Further, there are individuals who are labeled as "bystanders" or "outsiders", who are neither targeted by the aggression nor do they participate in it. Recent empirical studies have confirmed the existence of perpetrators/victims, assistants, and different forms of bystanders in the cyberbullying context (e.g., Schultze-Krumbholz et al 2018a). Prevention researchers have especially focused on the role of bystanders due to their influence on social norms of the entire group and the indirect reinforcement of aggressive acts through a perceived passive consent to what is happening (Paluck and Shepherd 2012).…”
Section: Introductionmentioning
confidence: 99%